Preliminary Study of Activated Carbon Filters for Pollutants Removal in Diesel Engines - Villegas, Pedro Julio (International Journal of Sustainable Energy and Environmental Research, 2016)
Pollutants removal from combustion gases during diesel engines operation is one of the most widely known environmental applications of activated carbons. In order to guarantee the successful removal of contaminants and pollutants on activated carbons, the development of new adsorbents has been increasing in the last few years. This paper presents a systematic study for cleaning diesel engines of CO, SO2, NO2 and H2S using the process of physical adsorption on novel adsorbents obtained from tropical biomasses. The combustion gases were qualitative and quantitative analyzed by Gas Chromatography. The use of this simple method is a valuable alternative to meet emission standards in Developing Countries. It was demonstrated that the agricultural wastes studied here are a feasible alternative for granular activated carbons preparation for pollutants removal during diesel engines operation, approaching its efficiency to the commercial Catalytic Converters.